Pengaruh Harga, Promosi, Kualitas Produk, Lokasi Dan Fasilitas Terhadap Keputusan Pembelian Perumahaman Di Wilayah Gentan Kabupaten Sukoharjo - Daironi, Imam, Sri Murwanti, SE., MM (2017)
The purpose of this study was to analyze the price has an influence on purchasing decisions, the promotion has an influence on purchasing decisions, product quality has an influence on purchasing decisions, the location has an influence on purchasing decisions, the facility has an influence on purchasing decisions and to analyze price, promotion, product quality , the location and the facilities together have an influence on purchasing decisions in the area of housing Gentan Sukoharjo district. The population in this study are all consumers of housing buyers who are in the area Gentan Sukoharjo and samples used in this study consumer purchaser of housing in the area Gentan Sukoharjo while sampling techniques using purposive sampling method. Based on the results of this study are known to exist significant price influence on purchasing decisions. There is a significant promotional effect on purchase decisions. There was a significant influence on the quality of the product purchase decisions. There is a significant effect of location on purchasing decisions. There was a significant effect of the facilities on purchasing decisions. No influence jointly price, promotion, product quality,